Ideal Surroundings: Domestic Life in a Working-Class Suburb in the 1920s - Morton, Suzanne (Studies in gender and history, 1995)
The 1920s are seen by historians as a crucial period in the formation of the Canadian working class. In Ideal Surroundings, Suzanne Morton looks at a single working-class community as it responded to national and regional changes. Grounded in labour and feminist history, with a strong emphasis on domestic life, this analysis focuses on the relationship between gender ideals and the actual experience of different family members. The setting is Richmond Heights, a working-class suburb of Halifax that was constructed following the 1917 explosion that devastated a large section of the city. The Halifax Relief Commission, specially formed to respond to this incident, generated a unique set of historical records that provides an unusually intimate glimpse of domestic life. Drawing on these and other archives, Morton uncovers many critical challenges to working-class ideals. The male world-view in particular were seriously destabilized as economic transformation and unemployment left many men without the means to support their families, and as the daughters of Richmond Heights increasingly left their class-defined jobs for service and clerical positions. Drawing on recent theoretical and empirical work, Morton expertly combines interpretive and narrative material, creating a vivid portrayal of class dynamics in this critical postwar era. Her focus on the home and domesticity marks and innovative move towards the integration of gender in the study of Canadian history. --Publisher's description
Keywords: 1900-1999; Families; Families Nova Scotia Halifax History 20th century; Familles Nouvelle-Écosse Halifax Histoire 20e siècle; History; Manners and customs; Nova Scotia Halifax; Nova Scotia Halifax Richmond Heights; Richmond Heights (Halifax, N.-É.) Moeurs et coutumes; Richmond Heights (Halifax, N.S.) Social life and customs; Rôle selon le sexe Nouvelle-Écosse Halifax Histoire 20e siècle; Sex role; Sex role Nova Scotia Halifax History 20th century; Suburban life; Suburban life Nova Scotia Halifax History 20th century; Travailleurs Nouvelle-Écosse Halifax Histoire 20e siècle; Vie de la banlieue Nouvelle-Écosse Halifax Histoire 20e siècle; Working class; Working class Nova Scotia Halifax History 20th century